Gradient estimates for Orlicz double phase problems with variable exponents. (August 2022) - Baasandorj, Sumiya; Byun, Sun-Sig; Lee, Ho-Sik
Abstract: Optimal regularity estimates are established for the gradient of solutions to non-uniformly elliptic equations of Orlicz double phase with variable exponents type in divergence form under sharp conditions on such highly nonlinear operators for the Calderón–Zygmund theory.